2013
DOI: 10.5688/ajpe778173
|View full text |Cite
|
Sign up to set email alerts
|

Home Medication Reviews in a Patient Care Experience for Undergraduate Pharmacy Students

Abstract: Objectives. To evaluate the effectiveness of conducting medication management reviews (MMRs) and home medication reviews (HMRs) on improving undergraduate pharmacy students' pharmaceutical care skills and clinical knowledge. Design. Fifth-year bachelor of science in pharmacy students were enrolled in a structured course in which MMR cases based on real patient scenarios were completed, findings were discussed in groups, and comprehensive feedback was provided by course instructors. Each student was then asked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
1
8
1
Order By: Relevance
“… Promote better patient compliance with medication regimens and dosages. Maximize health outcomes from treatment provided [ 47 - 51 ]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… Promote better patient compliance with medication regimens and dosages. Maximize health outcomes from treatment provided [ 47 - 51 ]. …”
Section: Introductionmentioning
confidence: 99%
“…Maximize health outcomes from treatment provided [ 47 - 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…Eleven of the 12 major theory talk articles assessed the impact of feedback on student learning. Seven articles evaluated the impact of a singular method of delivering feedback [audio-verbal [ 38 , 39 ], objective rubric [ 40 ], online ( n = 90 s and third-year PharmD (P2-P3) and 410 first-year PharmD (P1) students over 5 years) [ 41 , 42 ], or written ( n = 133 fifth-year BPharm students and 150 MPharm) [ 43 , 44 ] on learning whereas four articles compared multiple methods of delivery including online vs. handwritten ( n = 169 first-year MPharm and 201 P3) [ 45 , 46 ], verbal vs. written (350 P2-P3) [ 47 ], and audio-verbal vs. written ( n = 75 P1) [ 48 ]. Only one major theory talk article evaluated the quality of feedback provided, comparing peer to faculty feedback ( n = 182 fourth-year BPharm) [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…can also be encouraged to give students a quick reference guide to identifying potential drug interaction in prescriptions. Some other studies focused on pharmacy students' knowledge of conducting medication management reviews after a comprehensive lecture [33] and pharmacy students' knowledge in comparison with medical students on pharmacology and pharmacotherapeutics [28]. Both studies reported pharmacy students' comparatively higher knowledge in the areas studied.…”
Section: Discussionmentioning
confidence: 99%